Rede em malha sem fio utilizando o dispositivo ESP-8266: aplicação e avaliação de desempenho em cenário de detecção de presença de veículos em estacionamentos - Souza, David Modesto de (Brasil, 2023)
As a consequence of easy access to wireless technologies and the development of low-cost microcontrollers, the Internet of Things (IoT) has gained a lot of space in our globalized world. In this work, some tests will be exposed in order to show the operation of the wireless mesh network (Wireless Mesh Network - WMN) and its particularities for sensing. In addition, the possibility of applying WMNs to detect parking spaces in vehicles is presented, a scenario in which wireless nodes can be connected at distances ranging up to about 120 meters. In the proposed WMN research, wireless communication was carried out using ESP-8266 devices equipped with a Wi-Fi communication radio, where the WMN shared the same credentials (Service Set Identifier - SSID, access password and port (Transmission Control Protocol/Internet Communication Protocol - TCP/IP) to transfer data in ad-hoc type networks, in which there is a connection only between the WMN nodes, or in networks with external access, where there is a gateway node for interconnection of the WMN with the internet. With the implementation of this Course Completion Work - TCC, it was verified, in an experimental way, the viability of the proposal for i) the creation of sensor nodes to detect vacancies in vehicular parking lots; ii) the creation of WMN using sensors nodes and message forwarding nodes; iii) performance evaluation of the proposed WMN, through the generation of connection/disconnection scenarios of network nodes and verification of fault tolerance scenarios from the creation of redundant communication paths.